Kajian concept image siswa pada materi matriks - Sulistina, Linita; Negara, Habibi Ratu Perwira (Mahesa Research Center, 2024)
The failure of students to solve matrix problems may be due to misconceptions in their concept image. Concept image encompasses cognition related to a concept, including mental representation, properties, characteristics, and cognitive processes associated with that concept. This study aims to understand students' concept image regarding matrices. The method used is qualitative with a phenomenological approach, conducted on 19 eleventh-grade students in a madrasah located in Narmada District. Data collection involves tests and interviews. Samples are selected through testing. Concept image is determined based on indicators, including aspects of mental representation, processes, and properties. The research findings reveal that Subject 1 has a strong concept image, demonstrated by their ability to relate matrix concepts to relevant contexts, internalize concepts well, and apply them in various situations. Conversely, Subject 2 has a weak concept image, struggling to form a clear mental representation of matrix concepts and facing difficulties in applying correct formulas and procedures. Therefore, it is essential to implement teaching approaches focusing on deep conceptual understanding and fostering a strongÂ concept image to enhance student comprehension.